Catatonia syndrome - Milinović, Milica; Todorovic, Marko (Halo 194 Scientific Journal of Emergency Medicine, 2020)
Catatonic syndrome is a occurs as part of mood disorders, catatonic schizophrenia, conversion disorders, neurological or metabolic disorders, toxic infections of the CNS, viral infections and autoimmune diseases. In the case report, the diagnosis of dissociative stupor can be made even though somatic symptoms because they potentiate other symptoms. Diagnosis was made for several reasons. Due to the existence of a temporal relationship between the onset of symptoms of the disorder and stressful events. Due to the deep reduction of voluntary movements, speech and normal reaction to light, noise and touch, with maintained normal muscle tone, body posture and breathing. The key developmental task, the patient’s transition from the phase of fusion with the mother and dependence on her to a state of increased independence. Diagnosis and therapy according to the order of urgency and severity clinical picture and after prolonged inpatient treatment is indicated drug therapy and psychotherapeutic support.